LIFE WILL SEE YOU NOW quit waiting for the light at the end of the tunnel and light that f cker... up for yourself. - OATTES, GAVIN (CAPSTONE PUBLISHING LTD, 2020)
Best selling author, award winning comedian and international keynote speaker Gavin Oattes challenges you to live life better than you have to, to never be afraid of your own style and to blow your own god damn mind for a change. Cast your mind back to that album that changed your life' The riffs, the hooks and the lyrics that blew your mind' That movie that moved your whole world and assured you that life was going to be special' Transporting you to a place you'd never been before, the opening chapter of that book that changed your life forever'' The hairs on the back of your neck stood, adrenaline rushed through your entire body with the weight of the world gone from your young shoulders. Energised, inspired, alive, all in and ready to turn up to this wonderfully f*cked up thing we call life. Close your eyes and remember that feeling right there in that moment' Life Will See You Now'is a rousing, uplifting anthem that will inspire you to put down your phone, rediscover what truly matters and completely rethink what 'making it' in life actually means.' A personal development title with a difference ' there's no step-by-step guide and no map to change your life ' instead, it provides you with hilarious, real life inspiration, motivation and energy to figure it out for yourself and rediscover that wee piece of magic you had when you were just five years old.' Oattes makes the argument ' backed by both positive psychology and an abundance of childlike wonder ' that in an anxious world ruled by pressure, ego and other people's expectations, we are all incredibly lucky to be alive at a time where kindness, gratitude, play and ice-lollies really do matter. Remember, you don't have to do what everyone else is doing...